Meanings beneath the skin : the evolution of African-Americans - Boone, Sherle L., 1946- (Rowman & Littlefield Publishers, 2012)
Meanings Beneath the Skin: the Evolution of African-Americans traces cultural and psychological transformations among Black people in America from the seventeenth to twentieth centuries. By exploring how the meanings that African-Americans attribute to the concept of race contributed to distinctiveness in their psychological and cultural traits, this book reveals the social and political implications of these transformations for relationships between African-Americans and other groups during the twenty-first century.</sp.